Development of a PMRI-Based Module Assisted by GeoGebra for Teaching Geometric Transformations at SMA Negeri 10 Gowa - Ainul Yaqin; Sri Sulasteri; Mardhiah (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to examine the development process of a PMRI-based module supported by the GeoGebra application for teaching geometric transformations, and to determine its validity, practicality, and effectiveness for students of class XIB at SMA Negeri 10 Gowa. The research employed a Research and Development (R&D) design, following the ADDIE development model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The resulting product is a PMRI-based instructional module integrated with GeoGebra for the topic of geometric transformations.The trial subjects were 21 students from class XIB. The instruments used in this study included expert validation sheets, student response questionnaires, teacher response questionnaires, learning implementation observation sheets, student activity observation sheets, and learning outcome tests. Findings from the limited-trial phase indicated that: (1) the validation scores for both the instructional materials and research instruments reached an average of 4.3, classified as highly valid, as all evaluated components fell within the interval 4 ≤ M ≤ 5; (2) the module demonstrated practicality, shown by the average student response rate of 90.4% and the teacher response rate of 90%, both categorized as positive; and (3) the module met the criteria for effectiveness, as evidenced by an average teacher performance score of 4.6 (very good), an average student activity percentage of 76% (good), and student learning outcomes achieving a mastery level of 85.8%. Based on the results of the limited trial, it can be concluded that the development of the PMRI-Based Module supported by GeoGebra for teaching geometric transformations at SMA Negeri 10 Gowa meets the established criteria for validity, practicality, and effectiveness.